2018
DOI: 10.1002/psp.2169
|View full text |Cite
|
Sign up to set email alerts
|

Exiting distressed neighbourhoods: The timing of spatial assimilation among international migrants in Sweden

Abstract: Different theoretical frameworks offer competing explanations for the settlement patterns and residential mobility of international migrants. Some highlight migrants' neighbourhood preferences, whereas others emphasise structural constraints in the housing market. This paper aims to test three theories on migrants' socio‐spatial mobility—the theories of spatial assimilation, place stratification, and ethnic preference—by investigating the extent to which migrants move away from distressed immigrant‐dense neigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 39 publications
6
40
0
1
Order By: Relevance
“…This indicates support for place stratification theory over the relatively simplistic view of spatial assimilation theory (e.g. Vogiazides 2018). Other studies that have not specifically looked into spatial assimilation or place stratification, but rather the reproduction of neighbourhoods via residential mobility, have found that immigrants do move away from distressed areas and that this mobility is socioeconomically selective (Andersson and Bråmå 2004;Andersson 2013;Bråmå and Andersson 2005;Bråmå 2008).…”
Section: Theoretical Background Previous Research and Hypothesesmentioning
confidence: 68%
See 3 more Smart Citations
“…This indicates support for place stratification theory over the relatively simplistic view of spatial assimilation theory (e.g. Vogiazides 2018). Other studies that have not specifically looked into spatial assimilation or place stratification, but rather the reproduction of neighbourhoods via residential mobility, have found that immigrants do move away from distressed areas and that this mobility is socioeconomically selective (Andersson and Bråmå 2004;Andersson 2013;Bråmå and Andersson 2005;Bråmå 2008).…”
Section: Theoretical Background Previous Research and Hypothesesmentioning
confidence: 68%
“…Bolt and van Kempen 2003). Spatial assimilation in the Nordic countries has mainly been studied from three perspectives: moving away from distressed immigrant-dense neighbourhoods (Vogiazides 2018;Macpherson and Strömgren 2013), moving to a neighbourhood considered higher status in socioeconomic terms (Wessel et al 2017;Magnusson Turner and Wessel 2013), and moving into homeownership as an indicator of integration (Magnusson Turner and Hedman 2014;Kauppinen, Andersen, and Hedman 2015;Kauppinen and Vilkama 2016). Most of these studies find some limited support for the spatial assimilation thesis 1 (although Wessel et al (2017) find a complete lack of spatial integration), but the studies that consider differences between immigrant groups find that variation between groups is insufficiently explained by socioeconomic attributes.…”
Section: Theoretical Background Previous Research and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studier av innvandreres boforhold er ofte fokusert på preferanser, ressurser og struktur i boligmarkedet (Van Kempen, 2003;Vogiazides, 2018). I tillegg til innvandrernes økonomiske ressurser handler dette om hvordan boligmarkedet fungerer der de er, og, for nykommere, om hvordan de navigerer i nye og kanskje ukjente kontekster.…”
Section: Teori Om Tilgjengelighetunclassified